2003
DOI: 10.1159/000070444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Calcium Carbonate-Based Dentifrice on Enamel Demineralization in situ

Abstract: Since the effect of calcium carbonate (CaCO3) based dentifrice on enamel demineralization is not clearly established, it was evaluated using the IEDT model described by Zero’s group in 1992. This study had a crossover design and 10 volunteers were submitted to 3 treatment groups: a negative control, brushing without dentifrice; an active control, brushing with silica-based dentifrice (SiO2/MFP group), and the experimental group, brushing with CaCO3-based dentifrice (CaCO3<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 11 publications
2
59
0
2
Order By: Relevance
“…However, in the absence of test plaque, the remineralization observed with the SiO 2 -based MFP dentifrice did not differ statistically from the negative control, but the CaCO 3 -based one did ( table 1 ). This result is not explained by the amount of free F -already present in the dentifrices, which was 98 g F/g in the SiO 2 -and 113 g F/g in the CaCO 3 -based dentifrices [similar to the values previously reported by Cury et al, 2003]. The CaCO 3 dentifrice is a source of Ca ++ ion, which would increase the saturation degree of saliva and enhance remineralization, similar to the effect observed in plaque-free specimens for dentifrice containing dicalcium phosphate dehydrate [Zhang et al, 1995].…”
Section: Resultssupporting
confidence: 86%
“…However, in the absence of test plaque, the remineralization observed with the SiO 2 -based MFP dentifrice did not differ statistically from the negative control, but the CaCO 3 -based one did ( table 1 ). This result is not explained by the amount of free F -already present in the dentifrices, which was 98 g F/g in the SiO 2 -and 113 g F/g in the CaCO 3 -based dentifrices [similar to the values previously reported by Cury et al, 2003]. The CaCO 3 dentifrice is a source of Ca ++ ion, which would increase the saturation degree of saliva and enhance remineralization, similar to the effect observed in plaque-free specimens for dentifrice containing dicalcium phosphate dehydrate [Zhang et al, 1995].…”
Section: Resultssupporting
confidence: 86%
“…19 There was greater formation of cariogenic biofilm when exposure to sucrose was 8x/day in comparison with 4x/ day. 15 In this study, the enamel blocks were exposed 8x/day to a 20% sucrose solution. All of the fluoride regimens tested exhibited decreased surface hardness.…”
Section: Discussionmentioning
confidence: 99%
“…For 1 minute during the volunteers' habitual oral hygiene with the experimental dentifrice, the appliances were removed and fluoride dentifrice slurry (1:3 w/w) was dripped onto the specimens. 15 After brushing, and before devices were put back into mouth, the volunteers rinsed their mouths with 10 mL of tap water for 10 s. This procedure was performed for all treatments. When fluoride mouthrinse was also used (T II), the volunteers were instructed to rinse their mouths with 10 mL of the solution for 1 minute immediately after nightly toothbrushing procedures after replacing the devices.…”
Section: Experimental Designmentioning
confidence: 99%
“…These calcium carbonate-based dentifrices, unique in Brazil, were tested in vitro (39) and in situ (40), and recently it was demonstrated that calcium carbonate might enhance the effect of fluoride present in the dentifrice (41), probably by its buffering properties and/or enhancement of calcium concentration in plaque (42). Irrespective of the abrasive used, Brazilian fluoride dentifrices have demonstrated ability to interfere with dental caries in in vitro (39,43) and in situ (40,44) studies.…”
Section: Role Of Fluoride Dentifricesmentioning
confidence: 99%